Improvement in word recognition following treatment failure for sudden sensorineural hearing loss - Taha A. Jan (KeAi Communications Co., Ltd., 2016)
Objectives: Patients with sudden sensorineural hearing loss (SSNHL) may have word recognition scores (WRS) that correlate with pure tone average (PTA). We hypothesize that there is a subset of patients with SSNHL who have improved WRS despite stable PTA. Methods: Retrospective case review at a tertiary otolaryngology practice. Results: We identified 13 of 113 patients with SSNHL whose WRS increased despite overall stable pure tone averages. There was an observed average improvement in WRS by 23.8 points in this patient cohort at follow-up, with mean initial PTA in the affected ear at 48.7 dB. Conclusions: We identify a novel cohort of SSNHL patients that have failed treatment as measured by PTA, but who have increased WRS over time. These data have implications for patient counseling and lend insight into the pathophysiology of SSNHL. Keywords: Sensorineural hearing loss, Sudden sensorineural hearing loss, Word recognition score, Pure tone average